"In Vitro Study for The Role of Saliva pH in Early Childhood Caries Prevalence (ECC) And Its Connection with Some Variables in Hama City" (Journal of Hama University, 2019)
Dental caries are considered as one of the most common chronic diseases. The study of prevalence and severity of dental caries conducted in a specific geographic area contributes in constructing necessary plans for treatment and prevention.This study aimed to determine the prevalence and severity of early-childhood caries and to define risk factors associated with ECC among Hama/ Syrian pre-school children add to relationship between saliva pH and ECC.The sample comprised 2030 children where they ranged in age from (3 to 6) years.A questionnaire was distributed and contained information on oral feeding habits, oral care and educational status of the mother.The results, and data analysis showed that the prevalence of ECC for pre-school children was 81.1%, and dmft = 4,91±3,86.This study showed a significant relationship between ECC and age of children, the educational status of the mother, feeding habits (quality and duration of feeding) add to night feeding. However, breastfeeding and gender didn’t have significant effect.